A Novel Robotic Monofilament Test for Diabetic Neuropathy - Chumpon Wilasrusmee; Jackrit Suthakorn; Claire Guerineau; Yuttana Itsarachaiyot; Vera Sa-Ing; Napaphat Proprom; Panuwat Lertsithichai; Sopon Jirasisrithum; Dilip Kittur (Asian Journal of Surgery, 2010)
The use of the Semmes-Weinstein (SW) monofilament test is recommended as a screening method for diabetic neuropathy. It offers an important chance to prevent further complications of diabetic foot. We aimed to develop a prototype Robotic Monofilament Inspector that can be used as a standard machine for screening of diabetic neuropathy. Methods: Development was divided into three parts: computer software, control box, and Robotic Monofilament Inspector. The examiner conducted the SW test (by hand and by robotic inspector), vibration perception threshold, and Toronto Clinical Scoring System without knowledge of patient information. The unpaired t test or Wilcoxon rank-sum test was used to determine the differences between independent groups in terms of continuous outcomes, while the χ2 test was used to determine categorical outcomes. Agreement between the various diabetic neuropathy tests was measured using the kappa statistic. Results: The SW test and vibration perception threshold were more valid tests for neuropathy than the Toronto test. The robotic test was in excellent agreement with the two former tests and appeared to be valid (kappa statistic, 0.35-0.81). Another indirect evidence for the validity of the robotic test was the finding that diabetic patients with foot ulcers had a higher prevalence of neuropathy (77% vs. 38%). This might indicate that the robotic test was more valid than the manual test. Conclusion: The Robotic Monofilament Inspector could be used as a simple screening machine. This prototype may be developed further for routine clinical use.